PERANCANGAN SISTEM KONEKTIFITAS INTRANET-INTERNET DENGAN MENGGUNAKAN KONSEP NAT - Purwandi, A.W. (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Intranet can be related to the Internet, and vice versa. To connect your intranet to the internet a lot of things to watch for the efficient and effective connectivity. Some important things that are addressing and internet security. Internet protocol used in the TCP / IP (Transmission Control Protocol / Internet Protocol), requires that every host or intend to connect computers into a network must have a unique IP address. So that when the intranet was about to be connected to the internet or any host computer that is connected must have an IP address in accordance with the rules of the addressing used in the internet. The concept of NAT (Network Address Translator) provides a solution to overcome the limitations of available IP addresses. Masquereding IP is the internet service which is the application of the concept of NAT that can reduce the demand for new IP addresses connecting ourselves into the internet and intranet can improve security. Masquereding IP is one of the additional capabilities on LINUX operating system. Keywords: TCP / IP, NAT Concepts, IP Masquerading, LINUX